Konstruksi Pengetahuan dalam Relasi Kuasa di Pondok Pesantren - Juhairiyah; Maimun; Sa’dud Darain, A.; Fitriyah, Eliyatul; Junaidi, Achmad (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to examine how knowledge is constructed within the dynamics of power relations at Subulus Salam Islamic Boarding School. Using a qualitative method with a case study design, this research explores the interaction between formal and cultural authority structures and their influence on teaching practices and epistemological processes. Data were collected through in-depth interviews, participant observation, and documentation analysis, and were analyzed using an interactive model. The findings reveal that power relations in the pesantren are predominantly shaped by the central role of the kiai, whose authority determines educational policies, the selection of legitimate knowledge, and the direction of students’ intellectual development. This authoritative structure creates a learning environment in which students tend to adopt a passive stance and have limited opportunities for critical engagement. However, the study also identifies emerging initiatives within the institution to encourage intellectual participation, promote dialogical learning, and strengthen students’ critical thinking skills. These efforts indicate a shift toward more transformative and participatory educational practices. Overall, this research demonstrates that balancing traditional authority with inclusive learning strategies is essential for enhancing the quality of Islamic education in pesantren while maintaining their cultural identity.